Akuntabilitas Keuangan Berbasis Website Pada Organisasi Pengelola Zakat - Kapijan, Muhammad Kapijan; Atikah, Siti; Lenap, Indria Puspitasari (Fakultas Ekonomi dan Bisnis Unram, 2024)
One way to apply accountability is through transparency in financial management. Transparency of financial management, especially religious organizations, is an absolute thing to do. Although conceptually and philosophically the source of money from religious organizations is a gift that has been made by every believer sincerely. Supposedly, when the gift has been made which is intended for God, then for whatever reason no accountability is needed. However, human nature is given the freedom to choose to be a good or bad person has given birth to biased behavior when given the trustor responsibility to manage other people's property. So the purpose of this study is to findout how accountability in financial transparency in zakat management organizations. The type of research used in this research is descriptive research with a quantitative approach. The population in this study were all national scale Amil Zakat Agencies and Institutions registered with the Ministry of Religion of the Republic of Indonesia. Determination of the type of sample used in this study using purposive sampling technique, so that a sample of 38 zakat management organizations was obtained. The results showed that the overall financial accountability of OPZ can be said to be quite accountable. This can be seen from the acquisition of the average percentage of disclosure of all components of the financial statements, from 20 OPZs that publish reports.